2020
DOI: 10.1161/circulationaha.119.042573
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Overexpression of PDE4B Blunts β-Adrenergic Response and Maladaptive Remodeling in Heart Failure

Abstract: Background: The cyclic AMP (adenosine monophosphate; cAMP)-hydrolyzing protein PDE4B (phosphodiesterase 4B) is a key negative regulator of cardiac β-adrenergic receptor stimulation. PDE4B deficiency leads to abnormal Ca 2+ handling and PDE4B is decreased in pressure overload hypertrophy, suggesting that increasing PDE4B in the heart is beneficial in heart failure. Methods: We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 54 publications
1
39
0
Order By: Relevance
“…In addition, heart-targeting systems would support the development of new therapeutic agent classes, such as PPI disruptors (peptides, small compounds) or nucleic acids (siRNA) [268][269][270]. Alternatively, gene therapy strategies using associated adenoviruses (AAVs) exhibiting preferential cardiac tropism would specifically direct expression of cAMP modulators/regulators (e.g., PDE, AC), peptides (e.g., PKI, PPI disruptors) or siRNA in the heart and could be considered as therapeutic options [259,271].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, heart-targeting systems would support the development of new therapeutic agent classes, such as PPI disruptors (peptides, small compounds) or nucleic acids (siRNA) [268][269][270]. Alternatively, gene therapy strategies using associated adenoviruses (AAVs) exhibiting preferential cardiac tropism would specifically direct expression of cAMP modulators/regulators (e.g., PDE, AC), peptides (e.g., PKI, PPI disruptors) or siRNA in the heart and could be considered as therapeutic options [259,271].…”
Section: Discussionmentioning
confidence: 99%
“…The GO and pathway enrichment analysis was of great importance for interpreting the molecular mechanisms of the key cellular activities in PCOS. RPS5 [37], RBM3 [38], BAK1 [39], NDUFC2 [40], NDUFS4 [41], NDUFS5 [42], UQCRFS1 [43], COX6B1 [44], NDUFA13 [45], PRMT1 [46], RDX (radixin) [47], EPHB4 [48], SYNE2 [49], DNAH5 [50], NEDD4L [51], PDE4B [52] and CTNND1 [53] plays a critical role in the process of cardiovascular disease, but these genes might be linked with development of PCOS. Ostergaard et al [54], Zi et al [55], Kunej et al [56], Van der Schueren et al [57], Jin et al [58], Emdad et al [59], Liu et al [60], Scherag et al [61], Shi and Long [62], Sharma et al [63], Parente et al [64], Saint-Laurent et al [65] and Lee [66] demonstrated that over expression of COA3, PHB (prohibitin), UQCRC1, COX4I1, IFI27, MTDH (metadherin), S100A16, SDCCAG8, GLI2, NTN1, NLGN2, FGFR3 and PTPRN2 could cause obesity, but these genes might be involved in progression of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…For the knockdown of GPR39 in the hearts of mice, an adeno‐associated virus 9 (AAV9) system was applied. AAV9‐mediated shRNA targeting control construct (AAV9‐shCtrl, 5′‐TTCTCCGAACGTGTCACGT‐3′) or GPR39 (AAV9‐shGPR39, 5′‐GCTCCACACGTTCCTCTTTGA‐3′) were generated as described previously (Ding et al, 2015; Karam et al, 2020). Briefly, to generate p. AAV.U6‐shRNA constructs, DNA fragments harboring U6 promoter‐driven shCtrl or shGPR39 cassettes were separately cloned into the ITR‐containing AAV9 plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…AAV9 was packaged in HEK293T cells with AAV9:Rep‐Cap and pHelper (pAd deltaF6), and the virus was purified and concentrated by gradient centrifugation. One‐week‐old male C57BL/6 mice received a single intravenous injection of saline or AAV9 vector via the jugular vein at a concentration of ≈1 × 10 11 viral genomes per mouse, as previously described (Ding et al, 2015; Karam et al, 2020).…”
Section: Methodsmentioning
confidence: 99%